Development of A Total Quality Management Assessment Model for Enhancing Teacher Learning Performance in Special Schools - Mufidah, Aulia Maya; Yusuf, Munawir; Widyastono, Herry (Universitas Sebelas Maret, 2023)
This study aims to develop a Total Quality Management (TQM) assessment model and comprehensively examine the implementation of TQM in Special Schools. The primary focus lies in addressing the needs of school principals and teachers, facilitating the enhancement of teacher performance through the model, and evaluating its predictive validity. The research method in this developmental study employed research procedures adapted from Borg and Gall and was organized into four stages. The preliminary study stage comprised library research and field surveys. The model development stage involved validating the model by experts and practitioners. Using a correlation test, the predictive validity stage examined the relationship between total quality management and teacher performance. This study concludes that the implementation of TQM falls within the medium category. There exists a significant 90% need among school principals and teachers in special schools for assessments related to total quality management, indicating its essential nature. The validation by experts demonstrates consistently high results across all categorization aspects. Similarly, the validation by practitioners also yields noteworthy outcomes within each categorization aspect. The correlation between total quality management and teacher performance has been established. In light of these findings, it can be confidently asserted that the developed learning model is suitable for practical application